The Scottish medieval towerhouse as lordly residence in the light of recent excavation (Proceedings of the Society of Antiquaries of Scotland, 1989)
Excavations at Threave and Smailholm argue against the conventional model of the free-standing and self-contained towerhouse by demonstrating the presence alongside of additional residential and service buildings. Analysis of the floor areas of three Douglas towerhouses (Threave, Newark and Hermitage) shows the accommodation within the towerhouse to have been inadequate for the needs of the Douglas family. A R